Role of a versatile peptide motif controlling Hox nuclear export and autophagy in the Drosophila fat body - Duffraisse, Marilyne; Paul, Rachel; Carnesecchi, Julie; Hudry, Bruno; Banreti, Agnes; Reboulet, Jonathan; Ajuria, Leiore; Lohmann, Ingrid; Merabet, Samir (Journal of cell science, 2020)
Hox proteins are major regulators of embryonic development, acting in the nucleus to regulate the expression of their numerous downstream target genes. By analyzing deletion forms of the Drosophila Hox protein Ultrabithorax (Ubx), we identified the presence of an unconventional nuclear export signal (NES) that overlaps with a highly conserved motif originally described as mediating the interaction with the PBC proteins, a generic and crucial class of Hox transcriptional cofactors that act in development and cancer. We show that this unconventional NES is involved in the interaction with the major exportin protein CRM1 (also known as Embargoed in flies) in vivo and in vitro. We find that this interaction is tightly regulated in the Drosophila fat body to control the autophagy-repressive activity of Ubx during larval development. The role of the PBC interaction motif as part of an unconventional NES was also uncovered in other Drosophila and human Hox proteins, highlighting the evolutionary conservation of this novel function. Together, our results reveal the extreme molecular versatility of a unique short peptide motif for controlling the context-dependent activity of Hox proteins both at transcriptional and non-transcriptional levels.
Gesehen am 12.11.2025